2008
DOI: 10.1016/j.dental.2007.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance and wear characteristics of veneered lithia-disilicate-based ceramic crowns

Abstract: Objectives-The objectives of this study were to characterize the clinical performance and wear characteristics of lithia-disilicate-based ceramic crowns.Methods-Thirty posterior crowns were made using the heat-pressing technique and lithiadisilicate-based core ceramic. Subjects were recalled annually. The quality of crowns and adjacent gingival tissues were examined using nine criteria for acceptability. All crowns were examined and ranked from 4 (Excellent) to 1 (Unacceptable) for each criterion. Impressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 24 publications
2
46
1
Order By: Relevance
“…Since dental materials should ideally present wear behavior similar to that of enamel, the wear of dental materials is usually characterized in relation to that of dental tissues. These considerations imply that restorative materials, such as ceramics, should not damage natural antagonistic teeth (Preis et al, 2011;Suputtamongkol et al, 2008). Unlike previous studies (Preis et al, 2011;Stawarczyk et al, 2013b;Stawarczyk et al 2013c), no fractures of the enamel antagonists were observed in this study.…”
Section: Two-body Wearcontrasting
confidence: 70%
“…Since dental materials should ideally present wear behavior similar to that of enamel, the wear of dental materials is usually characterized in relation to that of dental tissues. These considerations imply that restorative materials, such as ceramics, should not damage natural antagonistic teeth (Preis et al, 2011;Suputtamongkol et al, 2008). Unlike previous studies (Preis et al, 2011;Stawarczyk et al, 2013b;Stawarczyk et al 2013c), no fractures of the enamel antagonists were observed in this study.…”
Section: Two-body Wearcontrasting
confidence: 70%
“…It is known that antagonist wear highly depends on the opposing ceramic materials [22] and the testing conditions [2]. Under clinical conditions, enamel antagonistic wear is shown to be higher than ceramic wear [23]. It is easy to understand that with varying force, sliding (roughness) and environmental conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since dental materials should ideally present wear behaviour similar to that of enamel, the wear of dental materials is usually characterized in relation to that of dental tissues. These considerations imply that restorative materials, such as ceramics, should not damage natural antagonistic teeth [18,25].…”
Section: Discussionmentioning
confidence: 99%